1890 Okla. Stat. 495, ch. 25, art. 47, § 1 - (:unkn) unknown (General Publisher, 1890)
It shall be unlawful for any person in the Territory of Oklahoma to carry concealed on or about his person, saddle, or saddle bags, any pistol, revolver, bowie knife, dirk, dagger, slung-shot, sword cane, spear, metal knuckles, or any other kind of knife or instrument manufactured or sold for the purpose of defense except as in this article provided.
--
Keywords: CARRY - CONCEALED